Tick-borne piroplasms and trypanosomes incidentally detected in eastern grey kangaroos (Macropus giganteus) during a mortality and morbidity event in southern New South Wales, Australia - Makenna Short; Kira Lowe; Michelle Michie; Ina Smith; Kim Blasdell; Alexander G. Maier; Alexander W. Gofton (International Journal for Parasitology: Parasites and Wildlife)
Tick-borne haemoparasites, including piroplasms and trypanosomes, are almost ubiquitous in Australian wildlife, with some associated with health impacts to individual animals and declining wildlife populations. An array of ecologically distinct piroplasm and trypanosome species occur throughout Australia although many of these species and their sylvatic ecologies are poorly characterised. Between May 2022 and October 2023, an anecdotally reported localised eastern grey kangaroo (Macropus giganteus) morbidity/mortality event occurred in coastal southern New South Wales, Australia, characterised by animals presenting with blindness, emaciation, lethargy, ataxia, and astasia. Here we used molecular techniques to identify tick-borne piroplasms (Babesia and Theileria) and trypanosomes in affected animals. Blood (n = 89) and liver (n = 19) samples were collected after the humane euthanasia of wild animals due to welfare concerns, and brief notes on the animal's health were recorded. In total, 20 (22.5%) animals were infected with tick-borne haemoparasites, including a novel Theileria sp. nov. (14, 15.7%), Babesia macropus (2, 2.2%), Trypanosoma gilletti (5, 5.6%), and Trypanosoma vegrandis (1, 1.1%). Liver samples were also screened for Wallal and Warego viruses due to animals' blindness, but were negative. This is the first report of T. gilletti and T. vegrandis in eastern grey kangaroos, although they have been previously reported in high numbers in ticks which commonly parasites this host. The novel Theileria sp. was previously reported in questing Ixodes holocyclus and in ticks from an opportunistically collected eastern grey kangaroo and red-necked wallaby (Notamacropus rufogriseus). However, we show for the first time this Theileria sp. can occur widely in eastern grey kangaroos. Ultimately, this small study did not intend, and is not able to draw inference regarding the pathogenicity of these haemoparasites to eastern grey kangaroos and it is likely that other factors, such as chronic Phalaris grass toxicity, had a role in this localised mortality/morbidity event.